Floor plan of John Ducey's house, Keels, NL. - Catherwood, Kristin; Millar, Edward; Whitney, Erin (2012)
John Ducey’s house is a two-storey structure that was built by four brothers: Thomas, James, David and John Ducey (John’s great-grandfather). Construction began in 1901 and was completed in 1903. It has been passed down from father to son through three generations. The house is laid out in a two-room kitchen/parlour plan with an unused front door between the main rooms on the ground floor. Directly facing the front door is a narrow staircase leading to the second floor. The upper storey contains three bedrooms with very low ceilings, typical of houses in the area. A linney extends from the north side of the house.